Visit from Fakultas Farmasi & Sains Universitas Muhammadiyah Prof. Dr. Hamka, Indonesia : fostering stronger collaborative ties / Norkasihan Ibrahim and Gurmeet Kaur Surindar Singh - Ibrahim, Norkasihan; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam, warmly received a delegation from Fakultas Farmasi and Sains Universitas Muhammadiyah, Prof. Dr. Hamka (UHAMKA), Indonesia, on October 24, 2023. This visit marked a significant milestone in the renewal of the Memorandum of Understanding (MoU) between the two institutions, focusing on academic, research, and cultural exchange. The visit not only reaffirmed the commitment to academic cooperation but also emphasised the shared vision of advancing pharmaceutical education and research.